Simulations of dissolved BTEX plumes migration derived from entrapped LNAPL - Teramoto, Elias Hideo (2019)
Accidental leakage of hydrocarbons represents a common  scenario of subsurfacial contamination. Once released, the hydrocarbon migrates until it reaches the vicinity of the uppermost portion of saturated zone, where it accumulates. Due to the fluctuation of the water level, the LNAPL (light non-aqueous phase) is redistributed and entrapped in the saturated zone. The entrapped LNAPL is responsible for the release of benzene, toluene, ethylbenzene and xylenes (BTEX) into the water generating the dissolved phase plumes of these compounds. The generated BTEX plumes vary in size and concentration over time in response to the depletion of BTEX compounds in the source zone. To represent this condition, a methodology was proposed that combines the use of the MODFLOW application for flow simulations, EXHAURIS to simulate mass transfer and MT3DMS to simulate solutes transport. The performed simulations were capable to reproduce the behavior of dissolved benzene and ethylbenzene plumes generated by jet fuel dissolution. Our results indicate that the benzene plume disappears within a period of 10 years, while the lifespan of ethylbenzene plume exceeds 20 years. This difference is related to the lower molar fraction and greater solubility of benzene as compared to ethylbenzene. The tests indicate that the proposed methodology is a promising alternative to predict the behavior of dissolved plumes over time contemplating the condition of depletion of the source zone.